Effect of cassava leaf meal (CLM) supplementation on growth performance of broiler chickens - Ab Aziz, Nur Laila (2016)
Cassava (Manihot esculenta) is a perennial woody shrub in the Euphobiaceace family, native to South Africa but now grown in tropical and subtropical areas as a source of food to people and also livestock. The cassava may grow until 2.75 meters tall, with leaves divided into 3-7 lobes. The cassava often grown as annual and propagated from stem cuttings after the tubers have been harvested. Fresh leaves contain hydrogen cyanide which may be toxic, but may be treated by soaking, fermentation or sun dried. The cassava leaves must be treated to reduce hydrogen cyanide, and they contains 20-30% protein which is the major source in feeding of animals. The treatment used in this experiment was by using sun drying and oven drying to reduce the hydrogen cyanide contents in cassava leaf. The cassava leaf was sun dried for about 24 hours and put in the oven for 1-3 days. The main objective of this project is to observe the effect of adding cassava leaf meal (CLM) to broiler diets on their growth performance. In this experimentation, feeding trials were conducted using three treatments to determine the effect of CLM on the broiler growth performance. The treatments are Treatment 1 (control), Treatment 2 (3 % of CLM added to the feed), and Treatment 3 (6 % of CLM added to the feed). The CLM added to the feed in each treatment starting from 22 days until 42 days. The feed intake and body weight were recorded weekly. The feed conversion ratio (FCR) recorded every week for each treatment. There is significant (P<0.05) difference of FCR for each treatment. For nutritional values, the feed sample from each treatment collected to conduct proximate analysis of each sample. The proximate analysis was observed the dry matter content, crude protein, and crude fat and crude fibre. From this experiment, Treatment 2 which is added 3 % of CLM in feed were effect on the growth performance of the chicken and have better FCR than Treatment 1 which is control, but for Treatment 3 not so good for broiler performance. In conclusion, the supplementation of cassava leaf meal were effects the growth performance of the broiler chickens.